Cognitive Impairment Associated with Schizophrenia: A Case Report - Jessica, Lia; Bessing, Yulia Fatima; Yulianti, Erikavitri; Salma Nur Fadhilah (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: First-generation antipsychotics could reduce the positive symptoms of schizophrenia but also impair cognitive function. Cognitive and negative symptoms in schizophrenia could be a significant burden experienced both by the patients and caregivers. Thus the treatment of cognitive impairment associated with schizophrenia should be addressed properly. The purpose of writing this article is to increase awareness in administering antipsychotics to elderly patients with schizophrenia, especially in the cognitive aspect and how to overcome possible cognitive decline. Case: An outpatient female schizophrenic patient who was on first-generation antipsychotic treatment complained of forgetfulness. The complaint started 5 years after she received her treatment. While she could still perform her activities of daily living independently, her instrumental activities of daily living were impaired. Her food got burnt while she was cooking, and she also took her medicine excessively because she forgot about it. Both of those events could be very dangerous for her. Discussion: Antipsychotics are the first-line pharmacotherapy for the treatment of schizophrenia but could also cause cognitive impairment. Management of cognitive impairment associated with schizophrenia could be performed both non-pharmacologically, by giving cognitive remediation therapy or physical exercise, and pharmacologically, by giving cholinergic agents such as donepezil. Conclusions: Cognitive impairment associated with schizophrenia should be managed as well as psychotic symptoms.